1968
DOI: 10.1099/00221287-52-3-421
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a Basic Amino Acid Permease in Neurospora crassa

Abstract: The system for transporting arginine into Neurospora conidia is described and shown to be consistent with the permease concept. The arginine system is shown to be separate from that which transports the aromatic and branched-chain neutral amino acids. Metabolic energy is necessary to achieve a concentration of arginine in the conidia higher than the external medium but not to maintain this concentration differential. A canavanine resistant mutant is shown to transport the basic amino acids at a reduced rate bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

1969
1969
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…The pmn; pmb; pmg strain of N. crassa is defective in constitutive amino acid transport by virtue of three single-gene mutations. The pmn mutation eliminates activity of the N system, the pmb mutation eliminates B system permease activity, and the pmg mutation eliminates the activity of the G system permease (15,28,29). The triple mutant was constructed in this laboratory and deposited with the Fungal Genetics Stock Center (Humboldt State University, Arcata, Calif.) as strain FGSC 2606.…”
Section: Methodsmentioning
confidence: 99%
“…The pmn; pmb; pmg strain of N. crassa is defective in constitutive amino acid transport by virtue of three single-gene mutations. The pmn mutation eliminates activity of the N system, the pmb mutation eliminates B system permease activity, and the pmg mutation eliminates the activity of the G system permease (15,28,29). The triple mutant was constructed in this laboratory and deposited with the Fungal Genetics Stock Center (Humboldt State University, Arcata, Calif.) as strain FGSC 2606.…”
Section: Methodsmentioning
confidence: 99%
“…Before growth on any of these compounds can occur, they must first be transported into the cells. A number of studies (5,15,19,21,22,25) have revealed in Neurospora the presence of at least four distinct amino acid transport systems specific for (i) L-neutral amino acids, (ii) L-basic amino acids, (iii) acidic amino acids, and (iv) a "general" system for both D-and L-neutral and basic amino acids. A system apparently specific for L-methionine has also been reported (16).…”
mentioning
confidence: 99%
“…At various time intervals portions were removed and the reaction was terminated by freezing. The samples were stored frozen, until analyzed by spotting 5-gliter samples on thin-layer plates (Eastman chromatogram sheet, cellulose with fluorescent indicator) which had been hand scored to 19 individual channels, 1 cm wide by 20 cm long. The samples were then chromatographed with ethanol: acetic acid: water (65:1:34) solvent for 160 to 180 *min.…”
mentioning
confidence: 99%
“…Mutations which cause an alteration in basic amino acid transport specificity include bat (18), hlp-l (3), and strain CR-10 which is resistant to the arginine analogue canavanine (13). In addition to the permeases with charge specificity, a general amino acid transport system with very broad substrate specificity has been described in Neurospora and found to be present under certain conditions (10).…”
mentioning
confidence: 99%